Effect of supervisor-subordinate Guanxi on employees work behavior: An empirical dynamic framework - Hira Salah ud din Khan; Yang Guangsheng; Muhammad Salman Chughtai; Matteo Cristofaro (Journal of Innovation & Knowledge (JIK), 2023)
Recently, the Chinese concept of guanxi (networks or business relationships) has drawn considerable attention and inspired researchers to explore its prevalence in diverse cultures. Accordingly, we examined the direct link between supervisor-subordinate guanxi and employee work behaviors (innovative work behavior and work engagement) by investigating the moderating effect of trust in the supervisor and the mediating effect of psychological empowerment. We collected data randomly from 510 employees (383 subordinates and 127 supervisors) working in China's manufacturing industry. The PROCESS macros operationalize the study constructs to test the presence of moderated mediation. All the hypothesized relationships are supported except the mediating role of psychological empowerment in the supervisor-subordinate guanxi and innovative work behavior relationships. The findings demonstrated that trust in supervisors strengthens the supervisor-subordinate guanxi's direct effect on psychological empowerment and its indirect impact on employees' work behaviors. To promote positive employees and work behaviors, organizations can develop supervisor-subordinate guanxi that supports organizational goals. Ethics statement This study was carried out in accordance with the recommendations of the Ethical Principles of Psychologists and Code of Conduct by the American Psychological Association's (APA). All participants gave written informed consent in accordance with the Declaration of Helsinki. The protocol was approved by the ethics committee of Jiangsu University, China.
Keywords: 650; Innovative Work Behavior; Psychological Empowerment; Supervisor-Subordinate Guanxi; Trust in Supervisor; Work Engagement